Urgensi Peraturan Mahkamah Agung Nomor 1 Tahun 2016 Tentang Pelaksanaan Mediasi Dalam Perkara Perceraian Di Pengadilan Negeri Surakarta - Thea Rizky Asa Perdana; Zakki Adhiliyati, S.H., M.H., LL.M (Sebelas Maret University, 2017)
This research aims to determine the urgency of change in the spreme court rule number 1 in 2016 on the impelemtation of mediation in courts, especially in divorce case at Religious Court of Surakarta where the success raet of mediation in divorce case is still very small. This research is an empirical law and applied with descriptive method. Data used is primary data obtained directly from the Religious Court in Surakarta. Secondary data were obtained from the materials library, books, journals, as well as the results of previous studies. The data collection technique is by interview and study documents or library materials and analyzed using qualitative analysis. The result of the research is that the success rate of mediation in divorce case in the Religious Court of Surakarta si still very small and its implementation hasn’t been effective based on Supreme Court Rule number 1 in 2008. Making the regulatory change become Supreme Court Rule Number 1 in 2016became the urgency for the religous court in Surakarta in order to increase the success of mediation and reduce the number of divorce in Religious Court of Surakarta. Keywords:Mediation, Divorce, Urgency, Religious Court